Acoustic and linguistic influences on rise-time modulations in natural English speech: evidence from a sensorimotor synchronization paradigm - Chia-Yuan Lin; Tamara Rathcke (Frontiers in Psychology)
Modulations of amplitude rise-time are considered fundamental to speech rhythm. However, rise-time is a holistic measure of the waveform shape and, as such, may be influenced by a variety of factors, potentially obscuring relationships between speech rhythm, signal acoustics, and linguistic structure. To address the factors that can modulate the rise-time of amplitude envelopes in English and the impact that rise-time modulations may have on rhythm perception in natural connected speech, we recorded 52 English sentences produced by a native female speaker and examined the effect of metrical weight, nucleus duration, average intensity, syllable onset complexity and sonority on rise-time duration in these sentences. As expected, amplitude rise-time was reflective of both acoustic-phonetic (nucleus duration and average intensity) and linguistic (onset complexity and metrical weight) factors. In addition, we conducted a sensorimotor synchronization experiment in which 31 native English speakers tapped in time with the beat of the recorded sentences. Analyses of synchronization showed that rise-time played a limited role in explaining rhythmic variability in these data. Taken together, the present findings indicate that rise-time cannot be straightforwardly mapped onto a specific linguistic function or a specific feature of the acoustic speech signal and is, therefore, difficult to interpret meaningfully. These results highlight a complex relationship between rise-time and speech rhythm and raise critical implications for speech rhythm research based on holistic acoustic measures such as rise-time.